Survei Efektifitas Implementasi Kurikulum Merdeka Pada Pembelajaran PJOK Di SMA, SMK, MA Kabupaten Bojonegoro - Moch Rico Al Afif; Mu`Arifin Mu`Arifin (LPPM Politeknik Pratama, 2023)
After the pandemic, the government has provided various innovations to revive education in Indonesia, one of which is by changing the curriculum. Previously using the 2013 curriculum and now changed to an independent curriculum. The independent curriculum provides freedom for schools and teachers to implement it. One of them is in the eyes of PJOK. In the implementation, of course, there will be various obstacles that will be faced by teachers, and the benefits obtained by teachers and students. Therefore, the purpose of this study is to find out how effective the independent curriculum is in PJOK learning. This research was conducted at high schools in Bojonegoro. The research method used is quantitative descriptive. This study used questionnaires and interviews to obtain data. The results of the study showed that the average teacher faced problems at the planning stage and confusion when planning projects to strengthen the profile of Pancasila. From the results obtained, it will be processed to determine the feasibility of implementing an independent curriculum. After the data was processed by the researcher, the results obtained were 75.5%. Based on the results and discussions that have been obtained, the implementation of the independent curriculum in PJOK subjects at high schools in Bojonegoro has been implemented, in some aspects the implementation has been implemented well, but aspects such as in the implementation of learning still need to be improved.